2005
DOI: 10.1042/bj20041577
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel human sperm-associated antigen 9 (SPAG9) having structural homology with c-Jun N-terminal kinase-interacting protein

Abstract: We report a novel SPAG9 (sperm-associated antigen 9) protein having structural homology with JNK (c-Jun N-terminal kinase)-interacting protein 3. SPAG9, a single copy gene mapped to the human chromosome 17q21.33 syntenic with location of mouse chromosome 11, was earlier shown to be expressed exclusively in testis [Shankar, Mohapatra and Suri (1998) Biochem. Biophys. Res. Commun. 243, 561-565]. The SPAG9 amino acid sequence analysis revealed identity with the JNK-binding domain and predicted coiled-coil, leucin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
97
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 46 publications
1
97
1
Order By: Relevance
“…26 Furthermore, our earlier MAPK interaction studies of SPAG9 with the JNK signaling pathway demonstrated that SPAG9 functions as a scaffolding protein. 16 The JNK signaling interaction is well known to play an important regulatory role in cell proliferation, differentiation, apoptosis, cellular transformation, and tumor cell growth, and may be equally important for the outcome of SPAG9 expression in the cervix. 16,27,28 To our knowledge, the mechanism underlying the association between SPAG9 and carcinogenesis is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Furthermore, our earlier MAPK interaction studies of SPAG9 with the JNK signaling pathway demonstrated that SPAG9 functions as a scaffolding protein. 16 The JNK signaling interaction is well known to play an important regulatory role in cell proliferation, differentiation, apoptosis, cellular transformation, and tumor cell growth, and may be equally important for the outcome of SPAG9 expression in the cervix. 16,27,28 To our knowledge, the mechanism underlying the association between SPAG9 and carcinogenesis is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…16 The JNK signaling interaction is well known to play an important regulatory role in cell proliferation, differentiation, apoptosis, cellular transformation, and tumor cell growth, and may be equally important for the outcome of SPAG9 expression in the cervix. 16,27,28 To our knowledge, the mechanism underlying the association between SPAG9 and carcinogenesis is still unclear. Perhaps the overexpression of SPAG9 changes the stability or kinetics of MAPK signaling pathways, leading to facilitation of cell invasion and migration; this warrants further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPAG9 is present in all but one sample in this study, and has been described to mediate JNK signaling. [34][35] For immunotherapy, expression in normal tissues raises concerns of generating autoimmune responses following vaccination. Still, some TS antigens, like MAGEA3, are targeted in current immunotherapeutic protocols.…”
Section: Discussionmentioning
confidence: 99%
“…9 Splice variants of JLP are known as JIP4 (Kelkar et al 2005) or SPAG9. 11 JIP proteins were first identified as scaffold proteins for specific JNK and p38 mitogen-activated protein kinase (MAPK) signaling modules. These proteins were also isolated as KLC-binding proteins and suggested to function as adaptor proteins linking cargoes to kinesin-1.…”
mentioning
confidence: 99%